Set of Laws and Decrees on Trade of Medicine - Egypt (2025)
Decree No.212/1960 -- Decree law No. 269/1960 -- Law No. 49/1961 -- Decree-Law No. 113/1962 -- Decree-Law No 13/1964 -- Law No. 13/1964 -- Law No. 10/1967 -- Decree No. 1253/1960 -- Ministerial Decree No. 463/1963 -- Decree No. 429/1976